The Competition of Dominant Powers in the International System and the US-China Encounter in the Horn of Africa (2012-2022) - Kaan Devecioğlu (Güvenlik Stratejileri Dergisi)
This study examines the power competition between the United States (US) and China in the Horn of Africa within the framework of Power Transition Theory (PTT). Using the concept of dissatisfaction, the study explores three main hypotheses: 1) the US as a satisfied dominant power and China as a dissatisfied rising power; 2) the US as a dissatisfied dominant power and China as a satisfied rising power; and 3) both actors being satisfied with the current international system. The Multiple Hierarchy Model is also applied when arguing these hypotheses. Through theorytesting process tracing, the study analyzes the geopolitical and geoeconomic implications of the competition in the Horn of Africa, focusing on military presence, technological infrastructure, regional disputes, and economic investments. The findings highlight how the strategic location of Djibouti and the Bab-el-Mandeb Strait plays a critical role in the US-China rivalry, influencing military strategies, telecommunications projects, and regional stability efforts. The study concludes that both the US and China engage in a mix of competition and cooperation, with significant impacts on the Horn of Africa’s political and economic landscape. This nuanced analysis contributes to the literature on PTT by providing empirical insights into the complex dynamics of US-China relations in a strategically vital region.